Taxation and Mobility: Evidence from Tax Decentralization in Italy - Enrico Rubolino; Tommaso Giommoni (Center for Economic Studies and ifo Institute (CESifo), 2023)
We study the impact of taxation on the location choices of individuals and tax bases in Italy. We exploit some recent tax decentralization reforms, which granted regions and municipalities greater power in setting income tax rates across brackets. Combining granular micro-level data on tax residence transfers with tax rate variations both within and across locations, we show that taxation significantly shapes location decisions. The mobility response greatly varies across the income distribution, with higher responsiveness among top incomes. Yet, our estimates imply that revenue losses due to tax-induced mobility are small, making local redistribution feasible at least over the medium-run.
Keywords: H24; H71; J61; 330; local income taxation; migration; tax decentralization